Ecofisiologia, zoneamento de risco climático e extensão rural com a cultura do gladíolo - Uhlmann, Lilian Osmari (2018)
The main objectives of the present work were (i) determine the radiation used efficiency (RUE) and its relationship with the air temperature and evaluate the dynamics of dry matter partitioning for gladiolus crop. (ii) Develop a climate risk zoning for gladiolus crop in Rio Grande do Sul state (RS), showing the adequate and inadequate planting dates using the PhenoGlad model and (iii) encourage the cultivation of flowers in the small family properties of the Central Depression of RS though extensive actions. Thus, were performed field experiments over the years 2012 until 2017 to determine growing of gladiolus crop, such as the radiation used efficiency and the dynamics of dry matter partitioning though collection of six plants of each developmental stage. The model PhenoGlad was used to determine the adequate and inadequate planting periods of gladiolus for 497 cities of RS, were used climate data from 34 years at 23 locations, considering different damage levels. A partnership with the rural extension institution, EMATER/RS-ASCAR, was started to identify producers interested in diversifying their production system and growing gladiolus. The dry matter partitioning of Gladiolus is modulated by two main sinks. The floral spike is the main sink until end of flowering and, thereafter the main sink becomes the new corm. Due to the two main sinks of gladiolus, the values of RUE for gladiolus (0.4310 g MJ-1 up to 0.9035 g MJ-1) are lower to other bulbous crops. The optimal temperature range for RUE in gladiolus is between 15 and 22°C. These parameters are important for the development of crop grown models in order to correct the growth rate under sub and supra-optimal conditions through a RUE response function. The gladiolus could be grown in all 497 cities of RS over almost all year, with exception in places that there is high probability of extreme temperature (low or high) at the critical phase of developmental cycle. In the coldest areas of the state, the inadequate planting period is between March and May, and at the hottest areas of the state, the inadequate planting periods are between October and January. Planting at the recommended periods is mandatory to produce high quality spikes. The gladiolus spikes have a demand of the consumers outside the All Souls day at Central Depression of RS. Regionalization of production reduces the cost of floral spikes to the final consumer, besides offering to the market higher quality products. This production system encourages short-chains market and contributes to the growth of flower production in the State of RS. Nevertheless, to ensure this, it is necessary to bring the results of research, with practical application, to the field through the link between research and rural extension.